2011
DOI: 10.1007/s11661-011-0681-4
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Direct Synthesis of WC-Co Nanocomposite Powder

Abstract: In this study, a novel method, termed dielectric-barrier-discharge-plasma (DBDP) assisted ball milling and low-temperature carburization, was used to synthesize WC-Co nanocomposite powder. X-ray diffraction, scanning/transmission electron microscopy, and differential scanning calorimetry were used to characterize the microstructure of powders. Starting from W, Co, and graphite powder mixtures, the DBDP-milled W-C-10Co powder exhibited a flakelike morphology with very fine lamellar structure. The WC-Co composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous work by our group [ 18–20 ] demonstrated that the use of a discharge plasma allows the fabrication of highly active W–C mixtures and promotes the reaction between W and C to form WC, thus lowering the reaction temperature of carburization. In the present study, TG‐DSC analyses of the nanocomposite powders were performed as a means of comparing their carburization processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work by our group [ 18–20 ] demonstrated that the use of a discharge plasma allows the fabrication of highly active W–C mixtures and promotes the reaction between W and C to form WC, thus lowering the reaction temperature of carburization. In the present study, TG‐DSC analyses of the nanocomposite powders were performed as a means of comparing their carburization processes.…”
Section: Resultsmentioning
confidence: 99%
“…Material Preparation: A milling device (PBMS, South China University of Technology, China) was used to prepare the WO 3 -C nanocomposite powders, based on working principles described in the previous publications. [18][19][20] A high-voltage alternating current power supply operating at 9.8 kHz and a maximum pulse voltage of 20 kV was applied to the ball milling jar using a single dielectric barrier discharge reactor. This current produced a homogeneous non-thermal Ar gas plasma in the milling jar.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ti-TiN nanocomposites were synthesized from raw atomized spherical CP-Ti powder with a diameter of about 15-53 µm (Changsha TIJO Metal Materials Co., Ltd., China) using a plasma milling device (PBMS, South China University of Technology, China). The working principle of this device has been reported previously [22][23][24][25]. In this work, mechanical ball milling was conducted during exposure to a homogeneous non-thermal N 2 gas plasma, which was generated with a pulse peak voltage of 25 kV and discharge frequency of 11.5 kHz using a single dielectric barrier discharge reactor.…”
Section: Materials Preparationmentioning
confidence: 99%
“…High-energy ball milling, utilizing mechanical energy, is a frequently used method to prepare ultrafine powders, alloys, or compounds in the solid state, and has attracted much attention in recent years [1][2][3]. During high-energy ball milling, the shear stress and impact will activate the material, which is called mechanical activation [4].…”
Section: Introductionmentioning
confidence: 99%